Ocular rosacea: Update on diagnosis and new therapeutic options - Camila Del Castillo; Guillermo Raul Vera-Duarte; Naomi Carolina Zatarain-Barrón; Nicolás Kahuam-López; Alejandro Navas; Enrique O. Graue-Hernandez; Arturo Ramirez-Miranda (The Pan-American Journal of Ophthalmology)
Ocular rosacea is a chronic inflammatory condition associated with cutaneous rosacea, affecting up to 72% of patients with the disease. Its pathophysiology involves genetic predisposition, immune dysfunction, neurovascular alterations, and microbiome dysregulation, leading to chronic ocular surface inflammation and epithelial barrier disruption. Clinically, it manifests as eyelid telangiectasias, blepharitis, meibomian gland dysfunction, and keratitis, with potential progression to scleritis or corneal neovascularization in severe cases. Despite its high prevalence, the variability in clinical presentation and the absence of specific biomarkers hinder timely diagnosis, increasing the risk of irreversible visual complications. Management follows a stepwise approach that includes eyelid hygiene, topical immunomodulators, and systemic antibiotics such as tetracyclines or macrolides for refractory cases. Recent advances have introduced novel therapeutic options, including intense pulsed light therapy, microbiome modulation, and matrix metalloproteinase inhibitors, offering a more personalized and effective approach to managing this condition.